Radical reorganization of existing work structures through digitalization - Duhan, Punita, 1973-; Singh, Komal, 1988-; Verma, Rahul, 1989- (Business Science Reference, 2018)
"This book explores how the 21st Century is the era of high-tech, digitized, borderless and networked economies and organizations. It explores how organizations are realigning, reshaping and reinventing themselves. It also provides understanding on the characteristics of networked enterprises, their pros and cons, critical success factors, reinvention strategies and envisaged changes"--